2018
DOI: 10.1007/s10864-018-09313-6
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Comparison of the Effect of Teacher Versus Self-Evaluation/Self-Reflection Feedback on College Students’ Behavioral Observation Skills

Abstract: An experimental investigation of the effectiveness of two types of feedback on college students' acquisition of behavioral observation skills was conducted. Special education and psychology students completed two training assignments involving behavioral observations of students engaging in problem behavior. Depending on the condition to which they were randomly assigned, participants experienced either teacher or self-evaluation/self-reflection feedback immediately after each assignment was completed. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…Optimizing the daily assessment format will be one of the individual study notes that are used as the basis for evaluating each student's learning. These results are researched (Desrochers et al, 2019) in developing a self-evaluation format that can be used a basis for student in improving learning outcomes. In the dance practice course in higher education, students' ability of to master dance materials with the correct technique needed to be taken seriously.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Optimizing the daily assessment format will be one of the individual study notes that are used as the basis for evaluating each student's learning. These results are researched (Desrochers et al, 2019) in developing a self-evaluation format that can be used a basis for student in improving learning outcomes. In the dance practice course in higher education, students' ability of to master dance materials with the correct technique needed to be taken seriously.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve these learning achievement standards, students need independent learning strategies that can be carried out outside of class hours so that learning outcomes can progress significantly at each meeting (Urban & Urban, 2019). Self-evaluation is an alternative learning strategy to provide feedback on learning outcomes at each meeting to increase student awareness in improving the weaknesses of their learning outcomes (Desrochers et al, 2019;Gibbs & Taylor, 2016;Griesbaum & Görtz, 2010;Doğan & Mirici, 2017;Oakes, 2020;Sumantri et al, 2018;Yan & Brown, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, researchers have shown that a positive environment promotes individual self-reflection, which subsequently cultivates critical thinking, strengthens in-depth learning (Mulvogue et al. , 2019) and improves individual learning ability (Desrochers et al. , 2019).…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Na pesquisa de Seufert, Guggemos e Sonderegger (2019), os autores questionaram os estudantes sobre suas percepções em relação à autoavaliação após o término do curso. Desrochers et al (2019) preferiram não discutir os impactos da autoavaliação de seu experimento ainda, e comentaram que é necessário aplicá-lo mais vezes. A quinta questão secundária de pesquisa preocupou-se em investigar como os autores entendem a acurácia da autoavaliação e como ela foi medida.…”
Section: Qsp04-contribuições Da Autoavaliaçãounclassified